ORGANIZATION OF HIGH-SPEED TRAFFIC WITH THE USE OF ROLLING STOCK WITH A FORCED TILT BODY CARS - Kurhan, M. B.; Korzhenevych, I. P.; Arsonov, V. V. (Science and Transport Progress, 2006)
An analysis has been conducted and the scope of usage has been established of rolling stock with a forced car body tilt.